Enhancing Security in Software-Defined Networking (SDN) based IP Multicast Systems : Challenges and Opportunities - Prasad, Preety (My University, 2024)
This thesis explores how software-defined networking (SDN) can enhance security in IP multicast, leading to efficient and secure content delivery within the broadcasting industry. Traditional multicast offers efficient data transmission but faces limitations in security and scalability. SDN-based IP multicast addresses these challenges through centralized control and programmability. However, new security threats emerge with SDN. This thesis proposes a framework for real-time event monitoring specifically tailored for securing IP multicast traffic within SDN environments. This framework leverages real-time analysis and pre-defined event monitoring policies to detect and mitigate security threats such as DoS attacks and unauthorized access. Additionally, the framework explores a mechanism for integrating with the SDN controller, enabling it to leverage the benefits of centralized control for automated responses like traffic rerouting or flow rule updates. The evaluation of the proposed framework demonstrates its effectiveness in improving security posture and reducing the risk of successful attacks on multicast communication. This approach, combined with robust security practices, ultimately enhances viewer experiences by ensuring the integrity, confidentiality, and availability of network resources and data transmission in modern broadcast environments.
Keywords: Multicast, data transmission, efficiency, bandwidth optimization, routing protocols, Software-Defined Networking (SDN), scalability, cybersecurity, threat attacks, routing protocol